THE DEVELOPMENT PROBLEMS OF BIOLOGICAL BEEKEEPING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Beekeeping is an integral part of the European agricultural production. More than 620 000 beekeepers work in the beekeeping branch of the European Union. Beekeeping is recognised to be an activity, which has an essential significance in the sustainable development of the rural areas, in the job-creation, the conservation of the ecosystem’s biological diversity, and in the maintenance of ecological balance. The basic principle of biological beekeeping is the production of as natural produce as possible. The study uses the analytical method to explore the current situation in the biological beekeeping sector. The analytical and comparative method helped to identify the problematic issues concerning the implementation of the beekeeping process and support measures. To study different views on the problems of biological beekeeping, the following methods for interpretation of legal norms were used: grammatical, systemic, teleological, and historical. The inductive and deductive scientific research methods were used to draw conclusions regarding current normative regulations and to recommend possible solutions.